2008
DOI: 10.1074/jbc.m708896200
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane Segment 6 of the Glut1 Glucose Transporter Is an Outer Helix and Contains Amino Acid Side Chains Essential for Transport Activity

Abstract: Experimental data and homology modeling suggest a structure for the exofacial configuration of the Glut1 glucose transporter in which 8 transmembrane helices form an aqueous cavity in the bilayer that is stabilized by four outer helices. The role of transmembrane segment 6, predicted to be an outer helix in this model, was examined by cysteine-scanning mutagenesis and the substituted cysteine accessibility method using the membrane-impermeant, sulfhydryl-specific reagent, p-chloromercuribenzene-sulfonate (pCMB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 32 publications
3
35
0
Order By: Relevance
“…In addition, a number of investigators have shown that cellular metabolism and ATP availability play a significant role in regulating GLUT1 expression and function through both direct and indirect mechanisms. Another report suggests that direct interaction of ATP with GLUT1-specific peptide sequences can lead to conformational changes that modulate transport of glucose and inhibit degradation of GLUT1 (18,35,36). Moreover, studies in skeletal muscle have shown that expression of a constitutively active form of AMP kinase (AMPK) results in increased GLUT1 and GLUT4 protein levels (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a number of investigators have shown that cellular metabolism and ATP availability play a significant role in regulating GLUT1 expression and function through both direct and indirect mechanisms. Another report suggests that direct interaction of ATP with GLUT1-specific peptide sequences can lead to conformational changes that modulate transport of glucose and inhibit degradation of GLUT1 (18,35,36). Moreover, studies in skeletal muscle have shown that expression of a constitutively active form of AMP kinase (AMPK) results in increased GLUT1 and GLUT4 protein levels (11).…”
Section: Discussionmentioning
confidence: 99%
“…The signaling pathways involved in acute insulin-stimulated GLUT4 translocation have been the subject of many studies over the past two decades. However, relatively few studies have examined the signaling systems involved in long-term regulation of GLUT1 mediated glucose uptake in noninsulin responsive tissues (4,5,11,18,36), and none of these previous reports have investigated the role of a signaling pathway that is an important regulator of cellular growth and metabolism, namely, the pathway that includes glycogen synthase kinase-3 (GSK-3), tuberous sclerosis complex (TSC), and mammalian target of rapamycin (mTOR).…”
mentioning
confidence: 99%
“…45,62,63 Cysteine scanning mutagenesis was subsequently employed to probe which residues lined this proposed central pore. [64][65][66][67][68][69][70][71][72][73][74] The resulting model indicated that TMs 2, 4, 5, 7, 8, 11, and possibly 1 and 10 formed a central aqueous transport channel for glucose, whereas TMs 3, 6, 9, and 12 formed a structural scaffold on the outside of the protein. 70 A possible substrate binding site was also proposed, involving Q161, Q282, and W412.…”
Section: Structure Of Human Glut1mentioning
confidence: 99%
“…V max /K m is obtained from measurements of 2-DG uptake and then normalized to cell surface GLUT expression to give k cat /K m . Although it is possible that TM6 mutants could alter the affinity (Ϸ1/K m ) of GLUT1 and GLUT4 for substrate, this seems unlikely because TM6 is a putative scaffold TM quite distant to the hypothesized GLUT1 substrate-binding cavity (25,26). Moreover, K m(app) for GLUT1-and GLUT4-mediated sugar uptake is similar for both 2-DG (9 -10 mM (63)) and 3-MG (ϳ6 mM (10)).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of GLUT crystal structures, our understanding of GLUT1 tertiary structure derives largely from scanning cysteine mutagenesis (22)(23)(24)(25) and modeling studies (26,27), which align and thread the GLUT1 sequence through the crystal structures of Major Facilitator Superfamily bacterial transporter homologs GlpT (28) and LacY (29). Although these homology-based threaded structures provide quite accurate descriptions of transporter topography and helix packing arrangements, they fail to accurately predict helix and amino acid side chain orientation within the active sites (30).…”
mentioning
confidence: 99%